PENETAPAN KADAR PENCEMARAN LOGAM Pb DAN Cr PADA IKAN NILA (Oreochromis niloticus) DI MUARA SUNGAI BADUNG - Bogoriani, N. W. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 1)
The study about determination of Pb and Cr content in nile fishes (Oreochromis niloticus) found at Estuaria Dam (Badung River Downtream) has been carried out. Some samples were taken every week during half a month. Five grams of dried sample was destructed with a mixture of 10 mL concentrated H2SO4 and 40 mL concentrated HNO3. The composition of Pb and Cr in the samples was analyzed Atomic Absorption Spectrofotometer using Standar Addition Method. The results showed that the content of Pb in the nile fishes was about 10.1910-10.7710 mg/kg wet samples and it was over the maximum level of 2.0 mg/kg. On the other hand, the content of Cr was found(1.3460-2.9640 mg/kg wet samples) to be out of level as well (maximum 0.4 mg/kg).
Keywords: nile fishes, Pb and Cr content.